637 Patients' Perceptions of Complications Following Thyroidectomy. (12th October 2021) - Marchitelli, G; Tingle, S; Bliss, R; Truran, P; Ramsingh, J
Abstract: Aim: The aim of this study was to assess patients' understanding of the risks of thyroid surgery and to assess whether their understanding of risks improved following the implementation of a pre-operative risk-tool. Method: Single centre prospective cohort study between June 2019-August 2019. All patients that underwent thyroid surgery were recruited. Patients had either the standard process of consent or were provided with a pre-operative risk-tool and information leaflet. Post-operatively all patients were provided with a questionnaire to determine their understanding of the risks involved in having thyroid surgery. Data was analysed using GraphPad Prism v6. Results: 51 thyroidectomy patients were recruited; 28 patients had a standard process of consent and 23 patients were provided with the risk-tool. Patients undergoing standard consent processes had a poor understanding of the magnitude of post-operative risk; their median score for risk magnitude was 4.5/10 (2-7) versus 8/10 (4-10) in the cohort receiving the risk-tool. The proportion of intervention to non-intervention participants giving the correct answer reached a statistically significant difference in 50% of questions asked (P < 0.001). Conclusions: It is imperative thyroidectomy patients are made aware of both rare events but also the frequency of which events occur so that they are properly informed prior to consenting. We have demonstrated that standard processes of consent in thyroidectomy patients leads to poor perception of risks; providing a surgical risk-tool can counteract this. These results warrant development of clear guidelines on the use of pre-operative surgical risk-tools in thyroidectomy patients.